Cause of Change on Carotid Intima-media Thickness - Waskito, Budi Arief (Universitas Wijaya Kusuma Surabaya, 2017)
Atherosclerosis causes significant morbidity and mortality. Carotid intima-media thickness (CIMT) can predict the onset of cardiovascular and ischemic stroke in the future. CIMT, the measurement of atherosclerosis, is determined in vivo using carotid ultrasound. CIMT is associated with traditional cardiovascular risk factors such as age, sex, race, smoking habits, alcohol consumption, exercise habits, blood pressure, dyslipidemia, dietary patterns, medications used, glycemia, hyperuricemia, anthropometric parameters associated with obesity. In addition, CIMT is also associated with novel risk factors, ie genotypes, cardiovascular anthropometry parameters, rheumatoid arthritis, immunologic diseases, inflammatory cytokines, lipid peroxidation, chemocyte anthropometric parameters, infectious diseases, vitamin D, matrix metalloproteinases, and other diseases